A framework of enabler's relationship for implementation of green manufacturing in Indian context. Issue 4 (19th May 2018) - Toke, Lalit K.; Kalpande, Shyamkumar D.
ABSTRACT: This study aims to recognize and select the appropriate strategy for implementing green manufacturing (GM) in Indian manufacturing industry by developing an instrument which could measure the progress of an organization towards the GM philosophy. This study identifies and analyses the key enablers behind the successful achievement of environmental sustainability in Indian manufacturing industry. Based on extensive literature review and discussions with experts, the critical success factors (CSFs) of GM have been identified. After examining the internal consistency of enablers, weightage is identified for finalizing the priority by analytical hierarchical process (AHP). The pairwise comparison method of AHP identified that top management commitment, green procurement practices and societal concern for protection of natural environment art the most important enablers, and competitiveness and availability of clean technology have comparatively less importance for the studied manufacturing industries. The purpose of this paper is to rank the enablers on identified weightage and develop the framework for offering the useful insights and guides about how industries should link CSFs of GM to improve the environmental and operational performance.